Taking back control?: investigating the role of immigration in the 2016 vote for Brexit - Goodwin, Matthew; Milazzo, Caitlin (SAGE, 2017)
The 2016 referendum marked a watershed moment in the history of the United Kingdom. The public vote to leave the EU –for a Brexit’- brought an end to the country’s membership of the European Union (EU) and set it on a fundamentally different course. Recent academic research on the vote for Brexit points to the importance of immigration as a key driver, although how immigration influenced the vote remains unclear. In this article, we draw on aggregate level data and individual-level survey data from the British Election Study (BES) to explore how immigration shaped public support for Brexit. Our findings suggest that, specifically, increases in the rate of immigration at the local level and sentiments regarding control over immigration were key predictors of the vote for Brexit, even after accounting for factors stressed by established theories of Eurosceptic voting. Our findings suggest that a large reservoir of support for leaving the EU, and perhaps anti-immigration populism more widely, will remain in Britain, so long as immigration remains a salient issue.